Application of Hospital without Wall Concept at the Dermatovenereology Services of Maria Walanda Maramis Hospital in North Minahasa - Lucky V. Waworuntu; Aaltje E. Manampiring; Gustaaf A. E. Ratag (Medical Scope Journal, 2022)
Abstract: Currently, a concept of health services by the hospital, Hospital without Walls, is intro-duced. This concept moves health services from the hospital to outside the hospital building. This study aimed to determine the application of the concept of a hospital without walls in Dermatovene-reology health services. This was a qualitative research design (grounded research) using informants through in-depth interviews, face-to-face and indirect. This study was carried out at Maria Walanda Maramis General Hospital, North Minahasa. Data were collected manually by making a transcript then were compiled in a matrix form and analyzed using the inductive analysis method. The results showed that the Hospital without Walls could be implemented, however, there were obstacles, internally and externally. The internal obstacles were that the hospital did not have a legal basis, SOP, and supporting facilities such as applications for this activity, payment for services of doctors and paramedics, professional human resources in the field of information technology to manage these activities. The external obstacles were the absence of regulation of BPJS for execution and payment of claims. In conclusion, the hospital without walls concept can be applied to the dermato-venereology health services at Maria Walanda Maramis General Hospital, North Minahasa, North Sulawesi Province.Keywords: Hospital without Walls; dermatovenereology services Abstrak: Saat ini berkembang suatu konsep pelayanan kesehatan oleh Rumah Sakit disebut Hospital without Walls yang memindahkan pelayanan dari Rumah Sakit ke luar bangunan Rumah Sakit. Penelitian ini bertujuan untuk mengetahui penerapan konsep Hospital without Walls pada pelayanan kesehatan kulit dan kelamin di Rumah Sakit Umum Maria Walanda Maramis Kabupaten Minahasa Utara. Desain penelitian ialah kualitatif (grounded research) dengan menggunakan informan (10 orang) melalui wawancara mendalam, secara langsung dengan tatap muka dan tidak langsung. Data yang terkumpul, diolah secara manual dengan membuat transkrip kemudian disusun dalam bentuk matriks dan selanjutnya dianalisis menggunakan metode analisis secara induktif. Hasil penelitian mendapatkan bahwa penerapan Hospital without Walls dapat dilaksanakan walaupun ditemukan hambatan secara internal dan eksternal. Hambatan internal ialah Rumah Sakit belum mempunyai dasar hukum, SOP, dan fasilitas penunjang seperti aplikasi untuk kegiatan ini, serta pembayaran jasa untuk dokter dan paramedis, SDM profesional di bidang informasi teknologi untuk mengelola kegiatan ini. Hambatan eksternal yaitu belum adanya regulasi BPJS untuk pelaksanaan dan pembayaran klaim. Simpulan penelitian ini ialah konsep Hospital without Walls dapat diterapkan pada pelayanan kesehatan kulit dan kelamin di Rumah Sakit Umum Maria Walanda Maramis, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara.Kata kunci: Hospital without Walls; pelayanan kesehatan kulit dan kelamin